Optimization of Advertising Tax Revenue Realization Through Taxpayer Collection by Surabaya City Regional Revenue Agency - Hildayanti, Siska Putri; Huda, Syamsul; Perdana, Putra (Pascasarjana Universitas Mataram, 2025)
The percentage increase in advertising tax realization based on data from the Surabaya City Regional Revenue Agency as of December 13, 2024 was 83.22%, this shows a large figure in the increase. However, the realization of advertising tax revenue must continue to be increased. This community service aims to increase the advertising tax revenue figure. This community service was carried out at the Surabaya City Regional Revenue Agency by involving several Bapenda employees through a series of advertising tax collection activities through a good approach to taxpayers. The results showed a large number of taxpayers paying, therefore there was an increase in advertising tax revenue. This step is innovative in the collection process between tax officers and taxpayers. Based on the existing results, it is recommended that good collection be implemented to increase advertising tax revenue.